Coverage of Kurdistan Parliament issues on satellite channels and their role in directing public opinion Channels (Rudaw - NRT - kurdsatnews) : As a model Research extracted from a PhD thesis - Ibtisam Ismail Kadr,; Tariq Jawhar Awla, (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This study aimed to identify the role of Kurdish satellite channels in covering Parliament sessions in directing public opinion, as well as the most important issues covered by the channels and the extent of their commitment to impartiality and objectivity in covering Parliament sessions and directing public opinion from the respondents' perspective. This study is significant because it is the first scientific study concerned with satellite channels coverage of parliament sessions in Iraq and the Kurdistan Region. The researcher used the survey method as one of the descriptive study methods for data collection and analysis, and the researcher relied on the questionnaire form as data collection tools, The questionnaire was filled out and returned by 550 elites in the society in the Kurdistan Region governorates, including politicians, artists, and university professors. The researcher found several results, the most important of which are: Respondents agreed that the three channels (Rudaw, Kurdsat News, and NRT) were (to some extent) objective in their coverage of the parliament sessions. Because of their affiliation, the three channels were also impartial in their coverage of parliament sessions and in directing public opinion. The study also discovered that the issue of (employee salaries and allowances) was one of the most important issues that drew the attention of satellite news coverage